Sutadi, Fauzi IMPLEMENTATION OF THE 2013 CURRICULUM OF ISLAMIC EDUCATION AT INTEGRATED ISLAMIC ELEMENTARY SCHOOL (SDIT) LOGARITMA IN KARANGANYAR KEBUMEN CENTRAL JAVA - Sutadi Sutadi; Fauzi (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2022)
Abstract The emergence of Integrated Islamic Elementary Schools (SDIT) is a solution to answer the needs of urban Islamic education for students to receive adequate Islamic education without going to Islamic boarding schools. This study aims to determine the content of the 2013 curriculum and the process of Islamic education implemented in Integrated Islamic Elementary School Logaritma. Data were collected through observation, interviews, and documentation. Data analysis was carried out by descriptive quantitative analysis with additional interview data. The results of this study indicate that the content of the 2013 curriculum in Integrated Islamic School Logaritama contains: 1) memorizing hadiths from class I to class VI as much as 48 hadiths; 2) memorizing 48 surahs of the Qur'an with 995 verses. While the process of Islamic education is carried out by: 1) memorizing hadith regularly at the beginning of learning process; 2) reading surah of the holy Qur'an using Ummi method; 3) reading sirah (story) of the prophets twice a week; 4) habituation of the dhuha (morning) prayer; and 5) the habit of praying in congregation.